2009
DOI: 10.1111/j.1365-2109.2008.02162.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of juvenile wedge soleDicologoglossa cuneata(Moreau) to high stocking density

Abstract: Physiological responses to a high stocking density were tested in juvenile wedge sole Dicologoglossa cuneata (Moreau). Fish were kept at low (1 kg m−2), medium (3 kg m−2) and high (9 kg m−2) stocking densities for 22 days. No differences in the weight, length, survival and hepatosomatic index were observed among treatments. Basal plasma cortisol and osmolality were found to be directly and positively related to stocking density. A mild increase in plasma glucose was seen at medium density, and plasma protein w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 35 publications
3
37
0
2
Order By: Relevance
“…TG is also an important source of energy during acclimation to different stocking densities (Herrera et al, 2009;Laizcarrión et al, 2012). The increase in serum TG under high density conditions could be related to lipid mobilization to cope with an increased energy demand when GLU stores are drastically utilized (Sheridan and Mommsen, 1991;Albalat et al, 2005;Huising et al, 2006), as shown by our results.…”
Section: Discussionsupporting
confidence: 58%
“…TG is also an important source of energy during acclimation to different stocking densities (Herrera et al, 2009;Laizcarrión et al, 2012). The increase in serum TG under high density conditions could be related to lipid mobilization to cope with an increased energy demand when GLU stores are drastically utilized (Sheridan and Mommsen, 1991;Albalat et al, 2005;Huising et al, 2006), as shown by our results.…”
Section: Discussionsupporting
confidence: 58%
“…However, our results showed a decrease in this parameter after 14 and 21 days of HSD in fed fish, in agreement with similar previous studies in P. pagrus reporting either a glucose drop within baseline levels (Fanouraki et al 2007) or non-significant changes Rotllant et al , 2003Van der Salm et al 2004). The enhanced plasma cortisol levels observed under our experimental conditions (see below) and the stimulation of hepatic glycogenolitic, gluconeogenic, and glucose export capacity induced by this hormone (Mommsen et al 1999;Laiz-Carrión et al 2002) Herrera et al 2009]. Both stressors (HSD and FD) tested in this study decreased plasma lactate and protein levels.…”
Section: Discussionmentioning
confidence: 52%
“…In teleosts, an enhancement of hepatic lipid metabolism, in order to cope with an increased energy demand, during HSD or FD conditions has been reported (Sheridan and Mommsen 1991;Albalat et al 2005;Polakof et al 2006;Herrera et al 2009). Present results (decreased plasma triglyceride levels and enhanced hepatic triglycerides values), obtained from specimens of P. pagrus under similar stressfully conditions, agree with this idea and suggested a mobilization of hepatic lipids as energetic source when protein and glucidic reserves are consumed in this organ.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have evaluated the effects of rearing densities on growth and metabolism in cultured fish species (Herrera et al, 2009;Li et al, 2012;Montero et al, 1999;Sangiao-Alvarellos et al, 2005). High biomass could activate stress response affecting negatively different metabolic pathways related to lipid, carbohydrate and protein metabolism (Costas et al, 2008;Laiz-Carrión et al, 2012), while low stocking densities could suppose, due to an inadequate use of space, higher production costs and lower profitability for the industry.…”
Section: Introductionmentioning
confidence: 98%